Harvey Bostwick Hurd (Editor), Revised Statutes of the State of Illinois. A.D. 1874, 360 (1874), ch. 38, § 56 - (:unkn) unknown (General Publisher, 1874)
Prohibited the carrying a concealed weapon, including a pistol, knife, slungshot, brass, steel, or iron knuckles, or other deadly weapon while disturbing the peace. Punishable by fine up to $100.
--
Keywords: CARRY - CONCEALED